The ventral striatum contributes to the activity of the motor cortex and motor outputs in monkeys - Suzuki, Michiaki; Nishimura, Yukio (Frontiers in Systems Neuroscience, 2022)
The ventral striatum (VSt) is thought to be involved in the vigor of motivated behavior and is suggested to be a limbic-motor interface between limbic areas involved in motivational processes and neural circuits regulating behavioral outputs. However, there is little direct evidence demonstrating the involvement of the VSt in motor control for motivated behaviors. To clarify the functional role of the VSt in motor control, we investigated the effect of reversible pharmacological inactivation of the VSt on the oscillatory activity of the sensorimotor cortices and motor outputs in two macaque monkeys. VSt inactivation reduced movement-related activities of the primary motor cortex and premotor area at 15–120 Hz and increased those at 5–7 Hz. These changes were accompanied by reduced torque outputs but had no effect on the correct performance rate. The present study provides direct evidence that the VSt regulates activities of the motor cortices and motor output.